REGENERATIVE IMMUNOLOGY: THE IMMUNOLOGICAL REACTION TO BIOMATERIALS - Cravedi, Paolo (Transpl Int, 2017)
Regenerative medicine promises to meet two of the most urgent needs of modern organ transplantation, namely immunosuppression-free transplantation and an inexhaustible source of organs. Ideally, bioengineered organs would be manufactured from a patient’s own biomaterials—both cells and the supporting scaffolding materials in which cells would be embedded and allowed to mature to eventually regenerate the organ in question. While some groups are focusing on the feasibility of this approach, few are focusing on the immunogenicity of the scaffolds that are being developed for organ bioengineering purposes. This review will succinctly discuss progress in the understanding of immunological characteristics and behavior of different scaffolds currently under development, with emphasis on the extracellular matrix scaffolds obtained decellularized animal or human organs which seem to provide the ideal template for bioengineering purposes.